You are on page 1of 12

Transition Probability Matrix

Recall our transition probability matrix, where p


ij
is
the probability of a transition to state j, given that we
are in state i
Suppose that the following matrix gives the transition
probabilities only for transient states, for a Markov
Chain with absorbing states:


Note that the rows do not necessarily sum to 1, because
there are other absorbing states not shown
Q=

11

1,

,1

,

Expected Time in a Transient State
Lets define m
ij
as the expected number of periods we
will spend in state j, given that we start in state i
Then we can define a matrix M of these values:
M=

11

1,

,1

,

Expected Time in a Transient State
Then we have:

For all i and j, where o
ij
= 1 if i = j, and 0 otherwise
The above is a set of (s m) x (s m) equations
In matrix form, we can write this set of equations as:
M = I + QM




=1

Expected Time in a Transient State
We would like to solve M = I + QM
This is equivalent to (I Q)M = I, or
M = (I Q)
-1

Thus, (I Q)
-1
gives us a matrix of m
ij
values
Element (i, j) of this matrix tells us the expected
number of periods we spend in state j, given that we
start in state i

Transitions to Absorbing States
Recall our definition of the R matrix:



The R matrix gives the transition probabilities from
transient state i to absorbing state j
Define b
ij
as the probability we end up in absorbing state j,
given that we start in transient state I
Lets define the matrix Q as consisting of q
ij
values and the
matrix R as consisting of r
ij
values to avoid confusion
columns columns
rows
0
rows
s m m
P
Q R
s m
I
m

=
(
(
(

Absorbing States
Define:

If we start in transient state i, three things can happen:
We transition to absorbing state j (with probability r
ij
)
We go to some other absorbing state (with probability



We go to transient state j (with probability q
ik
)
B=

11

1,

,1

,

Transitions to Absorbing States
The probability that we end in absorbing state j, given
that we start in transient state i, b
ij
, is:
b
ij
= Prob{we go to absorbing state j in one transition
(we go to some other transient state k we end up in
absorbing state j given that we start in transient state k)}
These are mutually exclusive events, so that the above
can be written as:
b
ij
= Prob{we go to absorbing state j in one transition} +
Prob{we go to some other transient state k we end up
in absorbing state j given that we start in transient state
k}

Transitions to Absorbing States
Next, note that transitions to the s m transient states
are mutually exclusive events, so that this can be
written as
b
ij
= q
ij
+ sum over all transient states k of Prob{we go to
transient state k we end up in absorbing state j given
that we start in transient state k}
Next note that the events {transitioning from transient
state i to transient state k} and {ending up in absorbing
state j given that we start in transient state k} are
independent events

Transitions to Absorbing States
This implies that we can rewrite this as:
b
ij
= q
ij
+ sum over all transient states k of Prob{we go to
transient state k} x Prob{we end up in absorbing state j
given that we start in transient state k}
The above can then be written as

=1
, for all i = 1, , s m, j = 1, , m
This is a set of (s m) x m equations

Absorbing States
In matrix form, we can write this set of equations as:
B = R + QB
Rearranging, we get (B QB) = R, or B(I Q) = R
Thus, B = (I Q)
-1
R
b
ij,
the probability of ending in absorbing state j, given
that we start in transient state i, is element (i, j) of
(I Q)
-1
R

Interesting Note
Consider the following matrix:
N = I + Q + Q
2
+ Q
3
+ + Q
n
+
This matrix has dimension (s m) x (s m); clearly this matrix
exists, right?
Now consider the quantity N(I Q)
N(I Q) = N NQ
= I + Q + Q
2
+ Q
3
+ + Q
n
+
Q Q
2
Q
3
Q
n

= I
Thus, because N(I Q) = I, this means N = (I Q)
-1
Therefore, (I Q) always has an inverse

You might also like